2013
DOI: 10.1111/1574-6941.12169
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effects of arabinoxylan oligosaccharides on juvenile Siberian sturgeon (Acipenser baerii) with emphasis on the modulation of the gut microbiota using 454 pyrosequencing

Abstract: The potential of a novel class of prebiotics, arabinoxylan oligosaccharides (AXOS), was investigated on growth performance and gut microbiota of juvenile Acipenser baerii. Two independent feeding trials of 10 or 12 weeks were performed with basal diets supplemented with 2% or 4% AXOS-32-0.30 (trial 1) and 2% AXOS-32-0.30 or AXOS-3-0.25 (trial 2), respectively. Growth performance was improved by feeding 2% AXOS-32-0.30 in both trials, although not significantly. Microbial community profiles were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 69 publications
(98 reference statements)
9
55
0
Order By: Relevance
“…The present results indicated that fish hindgut bacteria adapt to dietary AXOS and OF, although the change was not that strong ( Figures 1 and 2). This results are in agreement with our earlier studies where we demonstrated a higher production of SCFA in fish fed AXOS with an avDP of 32 versus short avDP of 3 [36]. We indicated that AXOS with a relatively longer DP have a stronger resistance to saccharolytic fermentation than AXOS with shorter DP.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present results indicated that fish hindgut bacteria adapt to dietary AXOS and OF, although the change was not that strong ( Figures 1 and 2). This results are in agreement with our earlier studies where we demonstrated a higher production of SCFA in fish fed AXOS with an avDP of 32 versus short avDP of 3 [36]. We indicated that AXOS with a relatively longer DP have a stronger resistance to saccharolytic fermentation than AXOS with shorter DP.…”
Section: Discussionsupporting
confidence: 93%
“…The predominant production of acetic acid by hindgut microbiota from Siberian sturgeon and African catfish in this study is in agreement with results for other fish and terrestrial animals, both in vitro and in vivo [4,9,36,42]. In carp, however, certain carbohydrate substrates resulted in high amounts of propionic acid during an incubation period of 6 h [22].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations